Study of the effect of ion irradiation on increasing the photocatalytic activity of WO3 microparticles - Kozlovskiy, Artem L.; Alina, Alua; Zdorovets, Maxim V. (Journal of materials science. Materials in electronics, 2021)
The work is devoted to the study of the possibility of using low-energy irradiation with helium ions to increase the photocatalytic activity of tungsten oxide (WO 3 ) microparticles, if used as catalysts for the decomposition of Rhodamine B. The prospect of this study is to find new ways to solve the problem of increasing the catalytic activity of micro- and nano-particles. During the study, the dependences of changes in the structural and morphological properties of the studied microparticles exposed to irradiation were established, and the effect of irradiation on the increase in the efficiency of decomposition of the organic dye Rhodamine B in aqueous media under UV irradiation was studied. It was found that the use of irradiation with helium ions leads to an increase not only in the rate of photocatalytic reactions, but also in the degree of mineralization, as well as in the efficiency of removing COD from aqueous solutions. Cyclic tests have shown the resistance of the modified microparticles to degradation, as well as the retention of the decomposition efficiency, with a decrease in the degree of mineralization after ten test cycles by 30%. At the same time, unlike the initial microparticles, ionic modification leads to an increase in the resistance of the structure to temporary degradation during cyclic tests.